Anticancer evaluation and molecular modeling of multi-targeted kinase inhibitors based pyrido[2,3-d]pyrimidine scaffold - Heba S. A. Elzahabi; Eman S. Nossier; Nagy M. Khalifa; Rania A. Alasfoury; May A. El-Manawaty (Taylor & Francis Group, 2018)
An efficient synthesis of substituted pyrido[2,3-d]pyrimidines was carried out and evaluated for in vitro anticancer activity against five cancer cell lines, namely hepatic cancer (HepG-2), prostate cancer (PC-3), colon cancer (HCT-116), breast cancer (MCF-7), and lung cancer (A-549) cell lines. Regarding HepG-2, PC-3, HCT-116 cancer cell lines, 7-(4-chlorophenyl)-2-(3-methyl-5-oxo-2,3-dihydro-1H-pyrazol-1-yl)-5-(p-tolyl)- pyrido[2,3-d]pyrimidin-4(3H)-one (5a) exhibited strong, more potent anticancer (IC50: 0.3, 6.6 and 7 µM) relative to the standard doxorubicin (IC50: 0.6, 6.8 and 12.8 µM), respectively. Kinase inhibitory assessment of 5a showed promising inhibitory activity against three kinases namely PDGFR β, EGFR, and CDK4/cyclin D1 at two concentrations 50 and 100 µM in single measurements. Further, a molecular docking study for compound 5a was performed to verify the binding mode towards the EGFR and CDK4/cyclin D1 kinases.